Risk of zidovudine-induced anemia on human immunodeficiency virus (HIV) infection patients with different CD4 cell counts - Anak Agung Ayu Niti Wedayani; Eti Nurwening Sholikhah; Erna Kristin; Erwin Astha Triyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Anemia is the most common hematologic abnormality in patients with human immunodeficiency virus (HIV) infection. This abnormality is associated with HIV infection itself, HIV-related opportunities infections or drug use. Zidovudine (AZT) is the most common cause of anemia in HIV patients. Recent study showed anemia in HIV patients is also associated with CD4 cell counts. Aim of this study was to evaluate the risk of anemia on HIV patients with different CD4 cell counts after AZT-based antiretroviral therapy (ART).This retrospective cohort study was conducted using medical record of HIV patients in Dr. Soetomo General Hospital, Surabaya. Subjects who fulfilled the inclusion and exclusion criteria were divided into two group i.e. HIV patients with CD4 cell counts 200-350 cell/mm3 and those with CD4cell counts ≥350 cell/mm3. All available demographics, clinical and laboratory data of subjects before and after AZT-based ART were then recorded and evaluated. Ninety-seven HIV patients (50 male and 47 female) were involved in this study. The result showed that the anemia incidence significantly increased after AZT-based ART (p<0.05), however no significantly different in anemia incidence, mean Hb level reduction and Hb level time reduction were observed between HIV patients with CD4 cell counts 200-350 cell/mm3 and those with CD4cell counts ≥350 cell/mm3(p>0.05). Gender, age, weight and clinical stage were not associated with anemia incidence (p>0.05). In contrast, anemia incidence is associated with Hb level before AZT therapy (p<0.05). In conclusion, the anemia incidence in HIV patients after AZT based ART is not associated with the level of CD4 cell counts, however it is associated with Hb levels before AZT therapy.